-5(-6-6d)=6(20d+20)

Simple and best practice solution for -5(-6-6d)=6(20d+20) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(-6-6d)=6(20d+20) equation:


Simplifying
-5(-6 + -6d) = 6(20d + 20)
(-6 * -5 + -6d * -5) = 6(20d + 20)
(30 + 30d) = 6(20d + 20)

Reorder the terms:
30 + 30d = 6(20 + 20d)
30 + 30d = (20 * 6 + 20d * 6)
30 + 30d = (120 + 120d)

Solving
30 + 30d = 120 + 120d

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '-120d' to each side of the equation.
30 + 30d + -120d = 120 + 120d + -120d

Combine like terms: 30d + -120d = -90d
30 + -90d = 120 + 120d + -120d

Combine like terms: 120d + -120d = 0
30 + -90d = 120 + 0
30 + -90d = 120

Add '-30' to each side of the equation.
30 + -30 + -90d = 120 + -30

Combine like terms: 30 + -30 = 0
0 + -90d = 120 + -30
-90d = 120 + -30

Combine like terms: 120 + -30 = 90
-90d = 90

Divide each side by '-90'.
d = -1

Simplifying
d = -1

See similar equations:

| 8n-21=6n+5 | | -33z+28z^2-28=0 | | 3x=3(x+6) | | 1/4(4x+8)=6(x-3) | | -6(6-12s)=6(-2+8s) | | -42.12=7.8t | | 5c+12-6= | | -x^2+6x+14=0 | | -20u+12.03=-18.5u-15.27-5.4u | | 3x+2(x+5)=4(x+6) | | 10(6t+1)-15=t-(t+4) | | 121-5x=13x+19 | | x^3+2x^2-x=o | | -13v-16.08=1.76+9.22-10.8v | | 6x-4y+11=0 | | 6r^2-7r-5=5 | | -(15r+15)=3(-4r+1) | | -3(-4x+2)=5(x-3) | | 3(x+3)+3x=4(x+6)+1 | | x^4+72x-20=0 | | 8x+12=68 | | 2+g=14 | | -4(-2+5)=6(x-3) | | 9n-(2n-3)=10 | | 44+55= | | 4y-10+y+54=8y+50-6y | | x-2y=21 | | -(10x+1)+3=-9+6x | | -4x+2=8x-26 | | 5x-7+x=4+5x | | 6x-6=4x+2 | | 20-n=10-2 |

Equations solver categories